LITERATURE REVIEW: CHARACTER VALUE DEVELOPMENT THROUGH CHEMISTRY LEARNING - Noviza Rizkia; Azzahrah, Suci; Nisa Kanahaya Br Tarigan (Program Studi Pendidikan IPA FIP Universitas Hasyim Asy'ari, 2025)
Chemistry learning is not only focused on mastering concepts and cognitive skills, but also holds significant potential in shaping and developing students' character values. This literature review aims to analyze various approaches and strategies in chemistry education that integrate character values such as responsibility, collaboration, honesty, and environmental awareness. The findings indicate that contextual approaches, project-based learning, and the integration of values in laboratory experiments are effective methods for instilling character values. Therefore, chemistry teachers need to design learning that is not only oriented toward academic outcomes but also toward character development as part of holistic education.